The moon phases influence on the beginning of astronomical dawn determination in Yogyakarta - Abu Yazid Raisal; Yudhiakto Pramudya; Okimustava Okimustava; Muchlas Muchlas (International Journal of Science and Applied Science: Conference Series, 2017)
In astronomy, there are three types of dawn. They are astronomical, nautical, and civil dawn. The sunlight is starting to appear on the east horizon when the Sun altitude is 18o below the horizon. Hence, there is a change on the sky brightness. The sky brightness can be affected by the moon phases. The sky brightness level is monitored by Sky Quality Meter (SQM). The SQM was installed upward to the zenith. There are 4 locations of measurement in Yogyakarta. The data has been collected for nine months to obtain the complete moon phases. The beginning of astronomical dawn is time when the sky brightness level is starting to decrease. The moving average algorithm was employed to determine the beginning of astronomical dawn. The time when the astronomical dawn begins is compared with the sun altitude calculation. The sun altitude calculation has been done using accurate times software. The difference of the beginning of astronomical dawn by measurement and calculation are 18.61±6.81 minutes, 19.12±3.28 minutes, 31.12±7.76 minutes, and 27.24±8.04 minutes, on the new moon (0), on the first quarter (0.25), on the full moon (0.5) and on the last quarter (0.75), respectively. The weather condition is also contributing to the results.